2012
DOI: 10.1038/ismej.2012.58
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Vibrio harveyi quorum sensing activity in real time during infection of brine shrimp larvae

Abstract: Quorum sensing, bacterial cell-to-cell communication, has been linked to the virulence of pathogenic bacteria. Indeed, in vitro experiments have shown that many bacterial pathogens regulate the expression of virulence genes by this cell-to-cell communication process. Moreover, signal molecules have been detected in samples retrieved from infected hosts and quorum sensing disruption has been reported to result in reduced virulence in different host-pathogen systems. However, data on in vivo quorum sensing activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 31 publications
3
49
2
1
Order By: Relevance
“…In this regard, it is worthy of note the study of Defoirdt and Sorgeloos [77], which proposed a possible integration of a host cue into the QS circuit. This cue might be represented by the local magnetic field.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it is worthy of note the study of Defoirdt and Sorgeloos [77], which proposed a possible integration of a host cue into the QS circuit. This cue might be represented by the local magnetic field.…”
Section: Discussionmentioning
confidence: 99%
“…The strains used for the AI-2 bioassay, Vibrio harveyi BB170 (HAI-1 negative; AI-2 positive; CAI-1 positive), V. harveyi JMH597 (HAI-1 negative; AI-2 positive; CAI-1 negative) [30], and V. harveyi JAF548, in which bioluminescence is not under the control of QS systems due to the permanent activation of the QS-dependent bioluminescence repressor LuxO [31,32], were cultured in LB supplemented with 30 μg ml −1 of the antibiotic kanamycin (LB+Km) and in autoinducer bioassay medium (AB) [33]. …”
Section: Methodsmentioning
confidence: 99%
“…V. harveyi BB170 (HAI-1 negative; AI-2 positive; CAI-1 positive), V. harveyi JMH597 (HAI-1 negative; AI-2 positive; CAI-1 negative), and the QS-independent bioluminescent strain V. harveyi JAF548 were used as biosensor strains [3032]. They were grown overnight in MB at 30°C with shaking.…”
Section: Methodsmentioning
confidence: 99%
“…We previously showed that the virulence of Vibrio harveyi BB120 (ϭ ATCC BAA-1116; recently reclassified as Vibrio campbellii [6]) in our model system with gnotobiotic brine shrimp larvae is regulated by quorum sensing (7). Using this model system, we investigated whether pyrogallol could protect challenged larvae from the pathogen and found that when added to the culture water at 10 mg · liter Ϫ1 or more, the compound significantly increased the survival of challenged larvae (Table 1).…”
mentioning
confidence: 96%